Protectionism - The key to growing a maritime industry? - Rauch, Diane-Maree (Shipping Law Unit, 2026)
Fourteen years after emerging from the oppression of apartheid, the South African economy is still ambling along to reach full development. Through various initiatives of not only government but also the private sector South Africa is continually striving to stimulate growth in the economy and shed its third world status.